2004
DOI: 10.1242/dev.01157
|View full text |Cite
|
Sign up to set email alerts
|

A role for MKP3 in axial patterning of the zebrafish embryo

Abstract: Fibroblast growth factors (FGFs) are secreted molecules that can activate the RAS/mitogen-activated protein kinase (MAPK) pathway to serve crucial functions during embryogenesis. Through an in situ hybridization screen for genes with restricted expression patterns during early zebrafish development,we identified a group of genes that exhibit similar expression patterns to FGF genes. We report the characterization of zebrafish MAP kinase phosphatase 3(MKP3; DUSP6 - Zebrafish Information Network), a member of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
135
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 72 publications
8
135
1
Order By: Relevance
“…In addition, we identified Mkp3 as a novel binding partner of Fbxl14a and Fbxl14b. Mkp3 is required for proper axial patterning during embryogenesis [8], and in agreement with this report, our data further indicated that Fbxl14a and Fbxl14b exert their functions during axis formation through differentially modulating Mkp3 ubiquitination and protein levels.…”
Section: Dear Editorsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, we identified Mkp3 as a novel binding partner of Fbxl14a and Fbxl14b. Mkp3 is required for proper axial patterning during embryogenesis [8], and in agreement with this report, our data further indicated that Fbxl14a and Fbxl14b exert their functions during axis formation through differentially modulating Mkp3 ubiquitination and protein levels.…”
Section: Dear Editorsupporting
confidence: 92%
“…Mkp3, which is involved in the determination of axial patterning of the early zebrafish embryo [8], was identified as an Fbxl14b-binding protein ( Figure 1D). Moreover, we found that Mkp3 also interacts with Fbxl14a ( Figure 1D).…”
Section: Dear Editormentioning
confidence: 99%
“…7,8 DUSP6 is a dual specificity phosphatase that intrinsically binds and inactivates MAPK1/ERK2 in a feedback loop manner 9 and plays an important role in physiological regulation of the signaling pathway of RAS and mitogen-activated protein kinases (MAPK). [10][11][12][13] In a previous report, we demonstrated that expressions of DUSP6 were reduced or abolished in cells of invasive ductal carcinoma of the pancreas in contrast to its overexpressions in dysplastic cells of pancreatic ducts. 8 Cultured human pancreatic cancer cells lacking an expression of DUSP6 tended to show constitutively active MAPK1, and an adenovirus-mediated introduction of DUSP6 into such DUSP6-inactivated cells induced inactivation of MAPK1, resulting in a marked growth suppression and eventual apoptosis of the cells.…”
mentioning
confidence: 81%
“…S1 and S2). In the zebrafish embryo, ier2 shows an FGF syn-expression group pattern at early stages (29,30) and is later detected in the notochord and caudal region, whereas fibp1 expression is ubiquitous (Figs. S3 and S4).…”
Section: Identification Of Ier2 and Physical Interaction With Fibp1mentioning
confidence: 99%
“…Fgf8 constructs are described in ref. 30, and dominant negative fgfr4 (dnfgfr4) was constructed by deletion of the intracellular domain of zebrafish fgfr4, and tested by its effects on several markers. Ier2 and fibp1 were amplified form cDNA libraries [a HeLa cell library was a gift from M. K Jang (National Institutes of Health, MD].…”
mentioning
confidence: 99%